LH/FSH Ratio Is Associated With Visceral Adipose Dysfunction in Chinese Women Older Than 55 - Zhao, Li; Zhu, Chunfang; Chen, Yi; Chen, Chi; Cheng, Jing; Xia, Fangzhen; Wang, Ningjian; Lu, Yingli (Frontiers in Endocrinology, 2018)
No study examined the association of luteinizing hormone to follicular stimulating hormone (LH/FSH) ratio with both visceral obesity outside the context of polycystic ovary syndrome. Thus, we hypothesized that the LH/FSH ratio was associated with visceral adipose accumulation and dysfunction among Chinese women older than 55. From 2014 to 2015, a total of 2,525 women aged 55–89 years were identified from a cross-sectional survey on the prevalence of metabolic diseases and risk factors in East China. Anthropometric indices, biochemical parameters, sex hormones and clinical characteristics were measured. Visceral adipose accumulation and function were identified by visceral adiposity index (VAI), Chinese visceral adiposity index (CVAI) and lipid accumulation product (LAP). Linear regression and logistic regression analyses were conducted to explore the association. A total of 1,462 (57.9%) participants had visceral obesity. In the linear regression, after full adjustment for demographic variables, metabolic factors, total testosterone (T), and estradiol (E2), LH/FSH ratio was positively associated with all indices estimating visceral obesity [B (95% CI): Log VAI 0.060 (0.030-0.090), Log CVAI 0.045 (0.029-0.061), Log LAP 0.103 (0.063-0.142), all P＜0.001]. Logistic regression analyses showed that the risk of visceral obesity increased with increasing LH/FSH ratio after controlling for age and smoking [OR (95% CI): 1.99 (1.52, 2.59), P＜0.001]. After further controlling for metabolic factors, the association was attenuated but remained significant [OR (95% CI): 1.89 (1.42, 2.53), P＜0.001]. The OR of visceral obesity in the fully adjusted model was 1.83 (95% CI 1.37, 2.45) ( P＜0.001). Thus, high LH/FSH ratio was significantly associated with visceral adipose over-accumulation and dysfunction in women over 55 years old. This ratio may be an early marker for metabolic disorders in Chinese women older than 55, which warrants further investigation.